Identification of Tyrosinase Gene Polymorphisms Associated with Albinism in Swamp and Riverine Types of Water Buffaloes (Bubalus bubalis Linn.) in the Philippines - Bacual, Melinda R.; Bacual, E.N.; Cruz, Y.C. Dela; Garcia, M.A.; Diaz, M.G.Q.; Flores, E.B. (Journal of Buffalo Science, 2024)
Background: Albinism is a genetic condition marked by a lack of melanin in the skin, hair, and eyes, leading to increased sensitivity to light and susceptibility to skin cancer. Oculocutaneous albinism in buffaloes is caused by a G>A mutation in the tyrosinase gene, which introduces a premature stop codon, rendering the enzyme inactive. Despite efforts to prevent genetic defects, albinism persists because it is an autosomal recessive trait. This study used capillary sequencing to analyze the tyrosinase gene in local buffaloes. Methods: One hundred forty-eight (148) buffaloes were sampled for genomic DNA extraction, followed by PCR amplification of the reported region of the tyrosinase gene with G>A mutation associated with albinism. The PCR products were subjected to Sanger chain termination sequencing. Genotypic frequencies were computed manually, and phenotypic association was done descriptively. Results: The proportion of phenotypically albino-looking buffaloes was 4.76% of the sampled animals and are homozygous for the A allele of the G>A mutation at position 1494 of the tyrosinase gene. These were all riverine-type buffaloes. Phenotypically white but with pigmented irises were all swamp buffaloes and comprised 4.17% of the sampled animals. All swamp buffaloes sampled, including the phenotypically white with pigmented irises, were homozygous for the G allele of the G>A mutation at position 1494, suggesting these are not similar cases of oculocutaneous albinism. Conclusions: The study established baseline data on the prevalence of albinism and identified new mutations in the tyrosinase gene for further research on their effects on color phenotypes and production potential.